Contested Public Spheres Female Activism and Identity Politics in Malaysia - Spiegel, Anna.; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2010)
This ethnographic monograph deals with women s organisations in an increasingly Islamised Malaysia and how they are fighting for women s rights and gender equality. Departing from an in-depth description of the life-world of female activists, Anna Spiegel highlights the significance of the global negotiations of gender relations for identity politics, the articulation of the local and the global within translocally acting social movements and the significance of globalisation for female agency. The study discusses the role of counterpublics in the development of subversive identity constructions and the renegotiation of the normative bases of publicness in the gendered fields of dress, cultural belonging, epistemic culture and Islam. Bringing together the global and the local, this is a global ethnography in the truest sense. This book is essential reading for researchers in the social sciences, in particular, cultural studies, subaltern studies, sociology, gender studies and Islamic studies. In addition, it is also of interest to scientists looking for new research methodologies in the study of globalisation.
Entering the World of NGOs -- Entering the World of NGOs: The Researcher s Trajectory -- Becoming an Activist: The Activists Trajectories -- Inside the World of NGOs: Constituting Female Counterpublics -- Negotiating Gender Equality and Legal Reforms: Women s Organisations in Kuala Lumpur -- Protecting Women s Dignity: Women s Organisations in Kelantan -- Defending the Quality of Life in a Global Economy -- Negotiating the Public Sphere in Local and Translocal Settings -- Mechanisms of Publicness: Dress, Cultural Belonging, and Education -- Constructing New Notions of Publicness -- Negotiating Rights within Diversity: Translocal Networking and Comparisons -- Conclusion: Translocal Knowledgescapes and Transnational Public Spheres.
Keywords: Social sciences; Sociology; Social Sciences; Sociology; Sociology